Las políticas de cuidado en América Latina: Articulando los derechos de las mujeres, ni\~nos, ni\~nas, adolescentes, adultos mayores y personas con discapacidades - Fernanda Wanderley (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2019)
– The right to care was recognized in the international regulatory framework. Its inclusion in the 2030 Agenda for Sustainable Development represented a fundamental step in the framework of global agreements. Goal 5 "Achieving gender equality and empowering women and girls" includes the mandate to "recognize and value unpaid care and domestic work". Goal 5.4 establishes the responsibility of States "to provide public services, infrastructure and social protection policies, under the co-responsibility approach of care". Similarly, policies and care programs are progressing in Latin American countries. The document represents the concept of care as a social right, analyzes the demographic, family and work transformations that demand a new social organization of care, and synthesizes progress in the region to achieve two objectives: to ensure access to care for children, adolescents, older adults and persons with family responsibilities.
Keywords: 330; Care; care policies; Latin America; gender equality; social rights; social protection; children; adolescents; seniors and people with disabilities; family responsibilities